2017
DOI: 10.1002/pros.23309
|View full text |Cite
|
Sign up to set email alerts
|

Abiraterone or Enzalutamide in Advanced Castration-Resistant Prostate Cancer: An Indirect Comparison

Abstract: There is strong evidence that enzalutamide outperforms AA with prednisone in terms of radiographic PFS and PSA progression and PSA response rate but not OS in the pre and post-docetaxel settings. These results may further guide clinicians in making treatment recommendations for patients with advanced prostate cancer. Prostate 77: 639-646, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
3
14
0
5
Order By: Relevance
“…Chopra et al performed indirect comparisons between ABI and ENZA in both pre-docetaxel and post-docetaxel settings based on published phase 3 RCTs [39] and found that ENZA outperformed ABI with prednisone in terms of radiographic PFS, time until PSA progression, and PSA response rate but not OS in both the pre-and post-docetaxel settings. The rate of adverse events of grade ≤3 was similar between ABI and ENZA.…”
Section: Discussionmentioning
confidence: 99%
“…Chopra et al performed indirect comparisons between ABI and ENZA in both pre-docetaxel and post-docetaxel settings based on published phase 3 RCTs [39] and found that ENZA outperformed ABI with prednisone in terms of radiographic PFS, time until PSA progression, and PSA response rate but not OS in both the pre-and post-docetaxel settings. The rate of adverse events of grade ≤3 was similar between ABI and ENZA.…”
Section: Discussionmentioning
confidence: 99%
“…Во-вторых, в отличие от оригинального исследования общая выживаемость (OS) и выживаемость без прогрессирования (PFS) в варианте «абиратерон» в настоящем исследовании определялись с учетом результатов непрямого сравнения энзалутамида и абиратерона по формулам: В настоящее время доступны результаты нескольких работ, в которых проводилось непрямое сравнение энзалутамида и абиратерона и рассчитаны необходимые ОР по указанным конечным точкам [10,11]. В обоих исследованиях получены выводы о статистически значимо более высокой эффективности энзалутамида по сравнению с абиратероном по критерию выживаемости без радиографического прогрессирования и отсутствии статистически значимых различий в показателях общей выживаемости.…”
Section: материалы и методыunclassified
“…Однако в 2017 г. было выпущено обновление резуль татов рандомизированного контролируемого исследования PREVAIL [13], в котором содержатся актуализированные данные по ключевым конечным точкам: общей выживаемости и выживаемости без радиографического прогрессирования. В этой работе длительность наблюдения при оценке общей выживаемости составила 45 мес, при оценке выживаемости без прогрессирования -36 мес (в более ранней публикации по исследованию PREVAIL [12], которая лежит в основе опубликованных непрямых сравнений [10,11], соответствующие периоды наблюдений составили 33 и 18 мес). В свою очередь, в последних опубликованных данных по абиратерону [14] длительность наблюдения при оценке общей выживаемости составила 35 мес и при оценке выживаемости без радиографического прогрессирования -33 мес.…”
Section: материалы и методыunclassified
“…Hormone‐dependency is another key issue in PCa pathogenesis as the condition depends on androgen receptor (AR) signaling. For this reason, advanced PCa is treated with androgen deprivation therapy (ADT; Chopra, Georgieva, Lopes, Yeo, & Haaland, ). However, nearly all ADT patients relapse and progress to CRPC.…”
Section: Prostate Pathologymentioning
confidence: 99%